2018
DOI: 10.4314/sokjvs.v16i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield losses and cost of clinical mastitis in Friesian × Bunaji crossbred dairy cows in Zaria, Nigeria

Abstract: Bovine mastitis is regarded as the most costly disease of dairy cows. Estimating its economic impact therefore gives farmers and veterinarians an insight into the costs of the disease at herd level and helps them make appropriate decisions regarding its control. The aim of this study was to determine the costs of clinical mastitis in Friesian × Bunaji crossbred dairy cows. Passive data collected between 2000 and 2015 was retrieved from the Dairy Research Programme of the National Animal Production Research Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Herd cost of lameness (HCL): Because all contributing cost variables were estimated at the herd level, the total herd cost of lameness was estimated as the sum of the cost variables (Moru et al, 2018) as shown in equation 6.…”
Section: 𝐶𝑃𝐶 = 𝐶𝑟ℎ − 𝑆𝑉𝑐 (5)mentioning
confidence: 99%
“…Herd cost of lameness (HCL): Because all contributing cost variables were estimated at the herd level, the total herd cost of lameness was estimated as the sum of the cost variables (Moru et al, 2018) as shown in equation 6.…”
Section: 𝐶𝑃𝐶 = 𝐶𝑟ℎ − 𝑆𝑉𝑐 (5)mentioning
confidence: 99%
“…An estimate of the economic impact of mastitis for 3 countries is presented in Table 1. Meanwhile, a few studies in Nigeria such as Moru et al [37] have attempted to estimate the economic loss associated with mastitis.…”
Section: Mastitis In Livestockmentioning
confidence: 99%
“…Economic losses to the dairy industry due to mastitis include reduced milk quality and quantity, veterinary costs, culling and deaths ( Degraves & Fetrow, 1993 ; Seegers et al , 2003 ). Subclinical mastitis is considered the most damaging and expensive due to the challenge in early detection ( Adamu et al , 2020 ) although studies on the economic impact of mastitis in both Ethiopia and Nigeria are lacking ( Adamu et al , 2020 ; Beyene & Tolosa, 2017 ; FAO, 2014 ; Mekonnen et al , 2019 ; Moru et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%